Chapter 3 An introduction to OpenFOAM - Mohammadian, Abdolmajid (Taylor & Francis, 2023)
Chapter 3 is an introduction to OpenFOAM, as the most popular CFD tool in effluent discharge modelling. A decade ago, OpenFOAM was only an academic tool for studying complex fluid mechanics problems. However, it has grown quickly in recent years and has found its way into industry as well (e.g., many consulting firms have invested in creating their own solvers for the particular problems they often solve). This book covers the fundamentals of OpenFOAM related to effluent discharge modeling: the choice of available solvers and differences between them, mesh generation options and methodology in OpenFOAM and postprocessing the numerical results.